Reimagining sustainability: The power of AI and intellectual capital in shaping the future of tourism and hospitality organizations - Bassam Samir Al-Romeedy; Thaib Alharethi (Journal of Open Innovation: Technology, Market and Complexity)
This research investigates the effect of artificial intelligence (AI) on organizational sustainability (OS) and delves into how this relationship is mediated by various dimensions of intellectual capital (IC), namely human (HC), structural (SC), and relational capital (RC). Data were collected from employees of Saudi travel agencies, resulting in 1122 valid responses, which were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that AI positively impacts OS as well as the three IC dimensions. Additionally, HC, SC, and RC have a positive influence on OS. The study also reveals that these dimensions partially mediate the relationship between AI and OS. This study advances the literature by clarifying how AI-enabled capabilities are translated into sustainable outcomes within the tourism and hospitality sectors. The findings offer valuable insights for industry professionals aiming to harness AI technologies for sustainable transformation. The study also offers strategic recommendations for tourism and hospitality organizations to invest in enhancing their IC, thereby optimizing the sustainability advantages of AI integration.